2021
DOI: 10.1177/2325967121990926
|View full text |Cite
|
Sign up to set email alerts
|

Injury Profile Among Street Workout Practitioners

Abstract: Background: Street workout (SW) is an urban sport based on calisthenic exercises. Injury profiles and risk factors are widely explored in various sport disciplines. However, because of the lack of research in SW, injury profiles have not yet been established. Purpose: To investigate the characteristics and prevalence of injuries and variables that may increase these odds in SW practitioners. Study Design: Case-control study; Level of evidence, 4. Methods: An electronic survey was conducted between September 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This syndrome is known to be a form of exhaustion caused by excess demands on energy, strength, or general resources, and it can affect all types of athletes [9]. It is important to report that such excesses can lead to a negative physical condition called overtraining, which in turn increases the exposure of athletes to injuries and discomfort [10].…”
Section: Introductionmentioning
confidence: 99%
“…This syndrome is known to be a form of exhaustion caused by excess demands on energy, strength, or general resources, and it can affect all types of athletes [9]. It is important to report that such excesses can lead to a negative physical condition called overtraining, which in turn increases the exposure of athletes to injuries and discomfort [10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, research on psychological profiles indicated that practitioners are predominantly young males motivated for health and their physical appearance (Taipe-Nasimba & Chirivella, 2020). Another study identified the injury profile, reporting that the most frequent diagnosis is tendinopathy, whereas the shoulders and the upper and midback are the most injured body parts (Ngo et al, 2021). Furthermore, a morphological study using anthropometry found that competitive SW athletes had a balancedmesomorphic somatotype, high development of upper limbs and trunk, high muscle mass levels, and low fat mass levels (Sanchez-Martinez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%